Project Based Learning (PjBL) Models with Folklore Nuance to Enhance Students' Writing Skills and Self-Confidence - Kurniasih, Hikmah Dwi; Mastur, Zaenuri; Juhana, Juhana (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the effectiveness of the PjBL model with folklore nuances to improve students' writing skills and self-confidence and to analyze the effect of self-confidence on students' writing skills in grade V. Currently, PISA shows that the ability of Indonesian students to solve PISA questions is still far above average value. For example, in PISA 2015, the performance of Indonesian students was still relatively low. Successively the average achievement scores of Indonesian students for reading, mathematics, and science are ranked 61st, 63rd, and 62nd out of 69 countries. The method used is a comparative method with a quantitative approach. The population of this study consisted of grade 5 elementary school students from the Ahmad Yani cluster in Adiwerna District, Tegal Regency, in the 2022/2023 school year, consisting of 10 elementary schools with a total of 375 students. The research sample consisted of 30 students from SDN Kaliwadas 01 and SDN Kaliwadas 02. The sample was selected using cluster random sampling. The two schools are located side by side. The data collection techniques used were questionnaires, interviews, and observations. The data sources used were primary and secondary. Primary data was obtained from the results of questionnaires, interviews, and observations. Secondary data was obtained through official releases or publications, including data used as literature such as books and reports. For data analysis techniques used are prerequisite analysis tests, namely normality test and homogeneity test, while hypothesis testing with t-test and simple regression test. Based on the results of the research, it can be concluded that there is an increase in the writing skills of fifth-grade students of SDN Kaliwadas 01 and SDN Kaliwadas 02 after using the folklore-based Project Base Learning (PjBL) method. In addition, PjBL, with the theme of folklore, also increases students' self-confidence, where folklore has high character education values, one of which is the character of self-confidence. Based on the research, it can be concluded that there is an increase in writing skills of 5th-grade students of SDN Kaliwadas 01 and SDN Kaliwadas 02 after the use of the Project Base Learning (PjBL) method based on folklore. In addition, PjBL, with the theme of folklore, also increases students' self-confidence, where folklore has high character education values, one of which is the character of self-confidence.